Influence of carbonaceous reinforcements on mechanical and tribological properties of PEEK composites – a review. Issue 12 (13th August 2022) - Sathishkumar, S.; Jawahar, P.; Chakraborti, Prasun
ABSTRACT: Nowadays, the Polymer materials play a niche role in engineering material industries because of their supportive and cooperative material properties like lightweight, less noise, self-lubrication behaviour, and cost-effectiveness, etc. In this case, the polymer materials do not give the desired properties individually, instead different types of fillers are added to increase the strength of the polymers. Among the different types of thermoplastic engineering polymers, in this manuscript PEEK (Poly Ether Ether Ketone)-based polymer composite is reviewed. Generally, the PEEK is one of the most significant chemical resistant polymers besides that it possesses favourable basic physical, mechanical, and electrical properties. PEEK semi-crystalline thermoplastic polymer possesses desirable thermal stability and is being used for high-performance engineering applications. Researchers have studied the influence of the various type of filler materials for improving the properties of PEEK. Our aim in this study is to review the influence of Carbon Nano Fibers (CNF), Carbon Nanotubes (CNT), and Graphene (G) as reinforcement in PEEK. This carbonaceous reinforcement is having a strength even greater than the strength of the steel, but its density is much lesser than steel. This character makes CNF-PEEK nanocomposites to be utilized in Aircraft applications. Likewise, carbon nanotubes and graphene are other predominant reinforcement materials used in making PEEK-based polymer composites. These reinforcements in combination make the PEEK nanocomposite system shield against electromagnetic interference and also enhance its electrical conductivity and thermal stability as well based on the method of distribution. The incorporation of carbonaceous nanoreinforcements in the PEEK matrix provides greater challenge and opportunity as well to produce a novel Nanocomposite with better physical and mechanical properties. In principle, an effective reinforcement for engineering application is expected to increase the mechanical and tribological behaviors of the composite system, which has been achieved by infusing the nano-reinforcements either directly or by performing different surface treatments on the nano-reinforcements. Considering the importance of PEEK-based composites in engineering application and also on considering the role of carbonaceous reinforcements in PEEK-based polymer systems, review on manufacturing aspects of CNF/CNT/GO-PEEK nanocomposites, role of nano-reinforcements in enhancing the physical, mechanical and tribological properties is presented in this manuscript.